2013
DOI: 10.1073/pnas.1222325110
|View full text |Cite
|
Sign up to set email alerts
|

Depth-profiling X-ray photoelectron spectroscopy (XPS) analysis of interlayer diffusion in polyelectrolyte multilayers

Abstract: Functional organic thin films often demand precise control over the nanometer-level structure. Interlayer diffusion of materials may destroy this precise structure; therefore, a better understanding of when interlayer diffusion occurs and how to control it is needed. Xray photoelectron spectroscopy paired with C 60 + cluster ion sputtering enables high-resolution analysis of the atomic composition and chemical state of organic thin films with depth. Using this technique, we explore issues common to the polyele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 57 publications
5
143
0
5
Order By: Relevance
“…The decoupled peaks showed roughly 66.7%, 16.7%, and 16.7% of areas under the C-C/C-H, C-N, and N-C¼O peaks [ Table II], which were in accord with the four C-C bonds, one C-N bond, and one N-C¼O bond in the monomer unit of pNIPAAm and those reported by others. 1,25,26 Since XPS typically probes the top 10 nm of the film, 40,41 it is possible to detect a small amount of Si and O from the APTES beneath the 5-6 nm retained pNIPAAm. However, this small amount of detected APTES, whose molecule contains two C-C bonds and one C-N bond, appeared to have little contribution to the break-down of C-C, C-N, and N-C¼O in the C1s peak of these samples.…”
Section: Potential Mechanism Of Retaining Pnipaam On Aptesmentioning
confidence: 99%
“…The decoupled peaks showed roughly 66.7%, 16.7%, and 16.7% of areas under the C-C/C-H, C-N, and N-C¼O peaks [ Table II], which were in accord with the four C-C bonds, one C-N bond, and one N-C¼O bond in the monomer unit of pNIPAAm and those reported by others. 1,25,26 Since XPS typically probes the top 10 nm of the film, 40,41 it is possible to detect a small amount of Si and O from the APTES beneath the 5-6 nm retained pNIPAAm. However, this small amount of detected APTES, whose molecule contains two C-C bonds and one C-N bond, appeared to have little contribution to the break-down of C-C, C-N, and N-C¼O in the C1s peak of these samples.…”
Section: Potential Mechanism Of Retaining Pnipaam On Aptesmentioning
confidence: 99%
“…2d). XPS is a sensitive surface analysis technique that measures the kinetic energy and number of electrons that escape from the top 10 nm of the material [15].…”
Section: Examination Of Signaling Molecules Involved In Cell Adhesionmentioning
confidence: 99%
“…Previously, our group has demonstrated that this technique can measure atomic concentration information as well as analyze interlayer diffusion and material exchange in nanostructured polymer thin films with a resolution around 15 nm. 18 Cluster-ion C 60 etching is much less damaging to polymers than single-ion etching methods commonly used for inorganic materials. 19 As shown in Figure 2a, the depth profiling process uses iterative C 60 + etching and XPS acquisition to probe the atomic concentration profile with depth.…”
Section: Axial Composition Analysis Usingmentioning
confidence: 99%